Harmony and development ASEAN-China relations - Lai, Hongyi 1965-; Lim, Tin Seng (World Scientific, 2007)
This book celebrates the 15th anniversary of China-ASEAN dialogue, which has captured the limelight as a key development in international relations in the Asia-Pacific. The contributions discuss a wide range of complex and challenging issues concerning ASEAN-China relations in a readable, informative, concise and comprehensive way. In three parts, the volume begins with an introduction and three speeches. The second and third parts discuss the political, security and economic aspects of ASEAN-China relations. Some of the specific issues covered in the book include China's rise and its implication on ASEAN, China's political and economic relations with ASEAN, and China's relations with Singapore, Malaysia, Indonesia, Vietnam, Myanmar and the Philippines.